The teacher perception on metacognitive strategies to enhance reading comprehension narrative inquiry - Karina Safitri Rachmawati (Jurnal Penelitian, Pendidikan, dan Pembelajaran, 2021)
ABSTRACT: Metacognitive strategies are one of the strategies used in the process of teaching and learning activity. This research aims is to know the teachers’ perception, experiences used metacognitive strategies for students to get better in reading comprehension. The results revealed that the participants acquired higher awareness and control in their strategy use. The purpose of conveying reading comprehension by using metacognitive strategies. By using the metacognitive strategy, the teacher can be easier to provide reading comprehension learning material for students and it can increase the value of reading comprehension. Teachers’ who use metacognitive strategies can positively impact students who have learning disabilities by helping them to develop an appropriate plan for learning information, which can be memorized and in the routine activity. (Djudin, 2017, p. 124)This research takes data by interview. This interview was designed so as to get information about participants’ perception, experiences and background knowledge which contained different questions about their skill teach use metacognitive strategies. Data were analyzed with coding process and the results revealed that participants compared two strategies there are discovery learning and metacognitive strategies to enhance students reading comprehension . The present study was conducted to understand the perception of one English teacher of grade eight students in School X regarding the metacognitive strategies to enhance reading comprehension students. Keywords: Metacognitive Strategies, Narrative Inquiry, Reading Comprehension